Applications and Performance Enhancement of 4D-Printed Shape Memory Polymers in Biomedical Fields - Wang, Xiangyu (Transactions on Environment, Energy and Earth Sciences, 2026)
Four-dimensional (4D) printing technology, combined with shape memory polymers (SMPs), permits controlled deformation of material constructs and thus finds applications across multiple disciplines. Due to favorable biocompatibility, this combined approach holds considerable promise for biomedical use. This review surveys recent advances in 4D-printed SMPs for biomedical purposes, focusing on applications such as tubular stents, bone tissue engineering scaffolds, drug delivery platforms, and biomimetic actuators. Current studies indicate that although 4D-printed SMPs generally exhibit acceptable biocompatibility for medical applications, their mechanical performance often falls short of clinical requirements. To overcome these limitations, the review categorizes enhancement strategies into two complementary directions: modifications of the 4D printing process and conventional material-level modifications of SMPs. It systematically summarizes prevailing approaches in both categories — for example, optimizing 4D printing parameters, alternating deposition of multilayer actuation materials, deliberate molecular-structure design, and physical blending — clarifies existing advances and limitations, and proposes a novel development pathway emphasizing “process–material” synergistic enhancement. These conclusions offer practical guidance for promoting the clinical translation of 4D-printed SMPs.